Linguagem e interação: argumentação e domínio semântico de determinação nos PCNS e no material didático do ensino médio - Gomes, Robert Moura Sena (Universidade Federal de São Carlos, 2019)
This work analyzed the Semantic Domain of Argumentation / Argument Determination in the National Curriculum Parameters (PCNs) and the courseware of the first year of high school, from the Language and Interaction collection, distributed by the Federal Government, by the National Textbook Program (PNLD) in 2018, to public schools. Was analyzed how these objects present the argumentation, in order to see if they are based on a rhetorical or linguistic point of view. It was also analyzed how these texts guide students in the study of argumentation. These materials have shown that even nowadays the rhetorical view of argumentation is present and majoritarian, as a practice in which a coherent life position is required, retaking the ethos of the one who argues as a true one, based on coherent points of view. It was shown that an in-depth study of the argumentation is of great importance, and that it is also important to propose how to study the argumentation not only from a rhetorical point of view but also from a linguistic point of view.
Language and interaction: argumentation and semantic domain of determination in PCNS and courseware
Keywords: Argumentação; Material didático; PCN; Domínio semântico de determinação; LINGUISTICA, LETRAS E ARTES::LINGUISTICA